(untitled) (Acta Judicial Journal, 2019)
The European Union has made a significant change in the personal data protection system. Until Regulation on the protection of natural persons with regard to the processing of personal data, each member state had the chance to regulate the protection of personal information what ment that the norms were significantly different among them. In order to contribute to a stronger system, the E.U. chose a Regulation to unify the basic principles and rights of European citizens in this matter. This paper conteains a review of the most significant improvements of the new European regulation and its consecuences in the Spanish law system.